Microcontrolled pyro-electric instrument for measuring X-ray intensity in mammography - de Paula, M. H.; de Carvalho, A. A. [UNESP]; Brassalotti, A. L. [UNESP]; Alter, A. J.; Sakamoto, W. K. [UNESP]; Malmonge, J. A. [UNESP]; de Almeida, Aparecido (Springer Nature, 2005)
A novel instrument for measurement of X-ray intensity from mammography consists of a sensitive pyro-electric detector, a high-sensitivity, low-noise current-to-voltage converter, a microcontroller and a digital display. The heart of this device, and what makes it unique is the pyro-electric detector, which measures radiation by converting heat from absorbed incident X-rays into an electric current. This current is then converted to a voltage and digitised. The detector consists of a ferro-electric crystal; two types were tested; lithium tantalate and lithium niobate. X-ray measurement in mammography is challenging because of its relatively low photon energy range, from 11 keV to 15 keV equivalent mean energy, corresponding to a peak tube potential from 22 to 36 kV. Consequently, energy fluence rate or intensity is low compared with that of common diagnostic X-ray. The instrument is capable of measuring intensities as low as 0.25 mWm -2 with precision greater than 99%. Not only was the instrument capable of performing in the clinical environment, with high background electromagnetic interference and vibration, but its performance was not degraded after being subjected to 140 roentgen (3.6 × 10 -2 C kg -2 air) as measured by piezo-electric (d 33) or pyro-electric coefficients. © IFMBE 2005.
Keywords: Mammography; Pyro-electric detector; Radiation; X-rayintensity; Clinical environments; Digital display; Electromagnetic interference; Energy fluences; High-sensitivity; Lithium niobate; Lithium tantalate; Low noise; Mean energy; Photon energy range; Pyro-electric detectors; X ray measurements; Detectors; Electric potential; Electromagnetic compatibility; Electromagnetic pulse; Lithium; Niobium compounds; X rays; Photodegradation